International comparison of liver transplant programmes: differences in indications, donor and recipient selection and outcome between Italy and UK. (4th May 2016) - Carbone, Marco; Nardi, Alessandra; Marianelli, Tania; Martin, Kate; Hudson, Alex; Collett, David; Romagnoli, Renato; Pinna, Antonio; Gimson, Alexander; Neuberger, James M.; Angelico, Mario
Abstract: Background & Aims: Comparing liver transplant (LT) programmes internationally can improve outcomes by stimulating cross‐national learning. Yet, comparison of crude outcomes, by using registry data, is limited by missing data, not allowing proper risk‐adjustment for donor‐ and recipient‐related factors. The objective of this study was to compare two European LT programmes based on high‐quality national longitudinal databases prospectively collected in Italy and UK respectively. Methods: We undertook a multicentre, international cohort study including all adults who underwent a first single organ LT in Italy ( N  = 1480) and the UK ( N  = 1003) between June 2007 and May 2009. Results: Italian donors were much older compared to the UK ones. Hepatitis C virus infection and hepatocellular carcinoma had higher prevalence in the Italian cohort compared to the UK one (47.5% vs. 23.1%, and 47.2% vs. 17.1% respectively). Centres' volume differed significantly, with five centres out of seven in UK vs. only two out of 20 in Italy performing >60 transplants per year. No national strategies to drive the donor–recipient matching were identified in both countries. After appropriate adjustment, a higher risk of early transplant loss was identified in the Italian cohort, whereas no differences were found in the 3‐year survival rates. Conclusions: International comparison of LT programmes provides the opportunity for benchmarking between heterogeneous healthcare systems and should ideally become a vital part of national quality assurance programmes. This requires the implementation of a standardized methodology for data collection to appropriately weigh each country's patient case‐mix and donor and recipients risk factors.